Perbedaan Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Dengan Tipe Stad Terhadap Penguasaan Seni Jurus Tunggal Baku Tangan Kosong - Afrizal Afrizal; Rimoni Desy (Universitas Negeri Padang, 2019)
The problem in this study is the lack of mastery of the training model of the stance of the trainer as an obstacle to the underdevelopment of athlete's achievement. In general, the trainer still tends to use only the conventional model, which is where the trainer has a full role in the training process, explaining and giving examples ahead with the command or command, while the athlete only relies on what is conveyed and exemplified by the coach without any cooperation or effort others to obtain the contents of the material presented. The research method used is quasi-experimental method. The number of people tried was obtained by the purposive random sampling method (conditional sample) was 16 people. The results of this study are: 1) There is a significant effect of the Jigsaw type learning model on the results of the standard single-handed stance art exercise. 2) There is a significant influence on the STAD type learning model on the results of the standard single-hand stance art exercise. 3) Jigsaw type learning model is more significant influence of the STAD type on the mastery of the art of a single hand standard.